Jacob Mincer Award (Journal of Labor Economics, 2021)
Previous articleNext article FreeJacob Mincer AwardPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreKenneth Wolpin is the 2021 recipient of the Jacob Mincer Award for lifetime contributions to the field of labor economics. Ken is emeritus professor of economics at the University of Pennsylvania, having recently retired from Rice, where was the Lay Family Professor of Economics and director of the Texas Policy Lab from 2016 to 2020. Previously, Ken spent 20 years at Penn, where he was the Annenberg Professor of Social Sciences. Ken was born in Manhattan in 1947, graduated from City College of New York in 1967, and worked as a high school teacher in Manhattan for three years before obtaining his PhD from City University of New York in 1974. On his committee were two former Mincer Award winners and a SOLE fellow, Finis Welch, Bob Willis, and Jim Smith. After a postdoc at Chicago, he spent several years at Yale, followed by professorships at Ohio State, Minnesota, and New York University.Ken Wolpin has made multiple contributions to labor economics, as a pioneer and leading exponent of dynamic structural modeling, as a pioneer in the use of natural experiments and application of theory to interpret them, and as a leader in the creation and improvement of key data sets. His 1984 Journal of Political Economy paper on fertility and child mortality was the first dynamic discrete-choice model of sequential decision-making under uncertainty ever estimated on panel data. His 1987 Econometrica paper on modeling school-to-work transitions of young men was another pioneering application of the dynamic discrete-choice approach. Wolpin’s 1989 Review of Economic Studies paper with Zvi Eckstein estimated the first structural model of women’s labor supply in which wages are endogenous because they are altered by work experience.Early work on dynamic structural models was limited by computational barriers. A 1994 Review of Economics and Statistics paper with Michael Keane used approximation and simulation methods to substantially enhance the richness of models that were feasible, in terms of both the number of decisions and the number of state variables. This work culminated in their 1997 Journal of Political Economy paper titled “The Career Decisions of Young Men,” which takes the human capital investment framework of Mincer and Becker seriously as a vehicle for explaining data on educational and occupational choices and labor supply. It has become a paradigm for subsequent structural work in labor. Substantively, it finds that the relevant skills that drive lifetime earnings are mostly attained prior to age 16, an idea that has been influential in shifting the focus of the human capital literature toward investments at younger ages. Eventually, a 2010 International Economic Review paper with Keane succeeded in extending the Mincer-Becker human capital investment framework further still by integrating marriage and fertility decisions into a model of the career decisions of young women.Ken achieved several other important “firsts” within the structural paradigm. His 1990 Econometrica paper with Eckstein was the first structural estimation of an equilibrium search model. His 1992 Journal of Political Economy paper was the first dynamic model where wages are driven by both work experience and job search. And his 2010 Econometrica paper with Donghoon Lee succeeded in placing the “career decisions” model in an equilibrium setting.Ken Wolpin’s leadership has also shaped the literature on natural experiments and data collection. Some of Ken’s most important work is at the intersection of labor and development economics. Ken’s 1980 Econometrica and Journal of Political Economy papers with Mark Rosenzweig used twins as a natural experiment to test the quantity-quality fertility model and to estimate the effects of fertility on female labor supply. And Ken’s 1982 International Economic Review paper used weather shocks as a source of exogenous variation to test the permanent income hypothesis. His 1982 Journal of Development Economics and 1986 American Economic Review papers with Rosenzweig exploited geographic variation of health and family planning interventions in India and the Philippines to show that these programs reduced fertility and child mortality, improved child health, and enhanced schooling of children. The latter paper was highly innovative in accounting for the endogenous location of interventions. Well ahead of its time, this work is some of the earliest in economics to leverage naturally occurring exogenous variation to test hypotheses and identify model parameters. In an important extension of this research program, a 2006 American Economic Review paper with Petra Todd used experimental data from Mexico’s Progresa program to validate a structural model of fertility and schooling.This is only a part of Ken’s enormous range of published work. He has an important stream of work on the estimation of production functions for child health and cognitive ability. This includes several papers with Rosenzweig and his widely cited 2003 and 2007 Economic Journal and Journal of Human Capital papers with Todd. There is also his work on fertility, intrahousehold transfers, labor market discrimination, the economics of education, and the economics of crime—the latter illustrated by his 2018 Review of Economic Studies paper with Chao Fu.Ken also made important contributions toward improving key data sets used by labor economists. As principal investigator of the National Longitudinal Surveys from 1983 to 1987 and director of the Center for Human Resource Research from 1985 to 1987, he made important contributions to the development of the National Longitudinal Surveys of Youth. He also served on the steering committee of the Health and Retirement Study from 2000 to 2004 and as an advisory board member for the Michigan Retirement Research Center (1999–2004), the Early Childhood Longitudinal Study (1996–97), the Panel Study of Income Dynamics (1983–86, 1994–2000), the High School and Beyond Survey (1990–92), and the National Longitudinal Surveys (1988–1995).Ken Wolpin’s numerous contributions to labor economics, which encompass theory, methodological innovations, careful applied work, and leading data collection, make him a truly worthy recipient of the Jacob Mincer Award.2021 Selection Committee:Richard Blundell (chair)Martha BaileyNicole FortinMike KeaneLance LochnerKathleen McGarry Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 39, Number 3July 2021 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/715497 Views: 1006Total views on this site © 2021 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.